2019
DOI: 10.1021/acs.jpcc.9b04503
|View full text |Cite
|
Sign up to set email alerts
|

Exergonic Intramolecular Singlet Fission of an Adamantane-Linked Tetracene Dyad via Twin Quintet Multiexcitons

Abstract: An adamantane-linked tetracene dyad (Tc-Ad-Tc) undergoes exergonic intramolecular singlet fission (SF), producing longlived (t = 175 µs) and high-energy (2 ´ 1.03 eV) multiexciton. Time-resolved absorption, fluorescence decay, and electron paramagnetic resonance (EPR) spectroscopic analysis revealed that the long-lived triplet species is generated in this system via correlated triplet pair having singlet and quintet characteristics. Time-resolved EPR analysis revealed formation of syn-and anti-conformers in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
74
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 53 publications
(78 citation statements)
references
References 63 publications
(135 reference statements)
4
74
0
Order By: Relevance
“…Dissociation time constants ranging from subpicosecond to microsecond regions are reported. [16][17][18][19][20][21][22][23][24][25] However little is known about how the T + T dissociation or the decoupling 12,16,24 occurs from the strongly coupled TT state.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dissociation time constants ranging from subpicosecond to microsecond regions are reported. [16][17][18][19][20][21][22][23][24][25] However little is known about how the T + T dissociation or the decoupling 12,16,24 occurs from the strongly coupled TT state.…”
Section: Introductionmentioning
confidence: 99%
“…1, the strongly coupled singlet TT state is known to be initially generated from the S 1 S 0 state. Generation of the quintet state in the triplet-triplet pair 17,22,23,[25][26][27][28] has been reported and is thought to be essential for preventing the loss of the SF-born multiexciton through the singlet channels. Using the timeresolved electron paramagnetic resonance (TREPR) method for TIPS-tetracene thin lms, Weiss et al 26 characterized the SFinduced strongly-coupled quintet of 5 (TT) in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Interacting triplet-pair states are key intermediates in photocatalysis [1], photon up-conversion [2], recombination in light-emitting diodes [3][4][5], as well as the process of singlet fission [6,7]-the production of two spin-1 triplet excitons from an initial spin-0 singlet exciton, a process which has received great interest for its potential in photovoltaics [8][9][10][11]. Recently, it has been demonstrated that the biexciton generated by the fission process can evolve in time to form a long-lived pair state with total spin S ¼ 2: a spin-quintet state [12][13][14][15][16][17][18][19]. This quintet state is intriguing for several reasons.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it was reported that covalently-linked dyads of π-conjugated systems have remarkably large tT. 12,14,22 To gain further insights into the TTA-UC of the three dyads, tT values of DPA-C1-DPA, DPA-C2-DPA, and DPA-C3-DPA in degassed CH2Cl2 were determined using PtOEPsensitized transient absorption analysis. The tT value for 3 DPA* was determined to be 190 µs by analysis of the 450-nm decay profile (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, new approaches that lead to improvement of the efficiencies of the TTA process are important because they are bound to serve as the basis of innovative strategies for the design of potentially important TTA-UC systems. By using time-resolved spectroscopic studies, several factors that improve the efficiency of singlet fission (SF, eqn 2), [10][11][12][13][14][15][16] the reverse of TTA, have been…”
Section: Introductionmentioning
confidence: 99%